EFEKTIVITAS PELAYANAN PUBLIK DIGITAL “APLIKASI GETUK SEWU” OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PRINGSEWU - Khasanah, Arifatun; Rosidah, Rosidah; Mosshananza, Hinfa (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2025)
The purpose of this study is to identify and explain the effectiveness of the digital service 'Getuk Sewu Application' by the Department of Population and Civil Registration of Pringsewu Regency. The background of this research is the effort to improve the quality of public services from the Department of Population and Civil Registration through the Getuk Sewu application. This writing theory uses the public service theory which refers to Zaithaml's perspective; service quality can be measured using five main dimensions, namely: reliability, tangibles, responsiveness, assurance, and empathy. The research approach adopted is qualitative, where the analysis process is conducted based on data obtained from collection techniques such as interviews, field observations, and document review. The research results indicate that the officers have demonstrated a good level of proficiency in operating the Getuk Sewu application. The presence of the Getuk Sewu application as a form of digital public service already reflects tangible indicators, particularly in terms of ease of access. Officials from the agency as well as village apparatus are considered capable of responding promptly to requests for civil administration services submitted by the community. The public feels confident and comfortable regarding the transparency of costs and the validity of the documents they receive. The conclusion of this study is that public services provided by the Civil Registration Office and village officials through the Getuk Sewu Application are quite effective, although they still face several obstacles. Keywords: Effectiveness; Getuk Sewu; Public Sevice.